Digital Competence in the Kindergarten Sector - Barbro Hardersen (Universitetsforlaget, 2012)
The kindergarten project at the The Norwegian Centre for ICT in Education will help to promote the development of digital competence in Early Childhood Education and Care and in pre-school teacher-training in a secure and professionally-oriented way. The main goal of the kindergarten project is to develop and strengthen use of ICT for improved quality, a better learning outcome and learning strategies for children in kindergartens and for students in pre-school teacher training. The key aim is to strengthen the digital competence of the entire kindergarten sector in the future. In December 2011 in Norway, 282,732 children attended kindergartens, and there were 88,823 employees in the kindergarten sector (Utdanningsdirektoratet 2012). Keywords: Kindergarten development, Early Childhood Education and Care and ICT, ICT in kindergarten-teacher training, digital culture of young children, pedagogical use of ICT in the kindergarten